Cardiotoxicity of BTK inhibitors: ibrutinib and beyond. Issue 4 (3rd April 2022) - Christensen, Bradley W.; Zaha, Vlad G; Awan, Farrukh T.
ABSTRACT: Introduction: The development of Brutons Tyrosine Kinase (BTK) inhibitors has transformed the treatment of B-cell malignancies and other non-malignant conditions. Management of the unique cardiotoxic profile of these agents requires prompt recognition and a multi-disciplinary approach. Areas Covered: The increasing indications and addition of newer agents to clinical practice and emergence of BTK inhibitor-related cardiac adverse events have complicated the management decisions for utilization of this class of therapy. We review the incidence, mechanisms, and management approaches for BTK inhibitor-related atrial fibrillation, hypertension, and ventricular arrhythmias. Expert Opinion: The newer BTK inhibitor acalabrutinib represents a new standard of care in front-line chronic lymphocytic leukemia (CLL) given the results of the ELEVATE-RR trial demonstrating comparable efficacy and a more favorable toxicity profile especially with regard to cardiac adverse events as compared to ibrutinib. Often not recognized by clinicians, BTK inhibitor-induced hypertension is common and can be severe, requiring prompt recognition and initiation or adjustment of anti-hypertensive medications to prevent major adverse cardiac outcomes. Novel BTK inhibitors in development are being designed to overcome the patterns of resistance from first-generation agents and to minimize off-target kinase activity, with promising toxicity profiles in early trials.